Fortune Favors the Bold: Introduction to the Special Series of the Vocational Rehabilitation Technical Assistance Center for Quality Employment. (April 2023) - Tansey, Timothy N.; Anderson, Catherine A.; Strauser, David; Bishop, Malachy; Chan, Fong; Wehman, Paul
This editorial provides an overview of the special series developed by the Vocational Rehabilitation Technical Assistance Center (VRTAC) for Quality Employment, H264K200003, and VRTAC-Targeted Communities (H264F15003) from the U.S. Department of Education, and in collaboration with the National Institute on Disability, Independent Living, and Rehabilitation Research project of Rehabilitation Research and Training Center (RRTC) on Employer Practices (#90RT5041), RRTC on Employment of Transition-Age Youth with Disabilities (#90RTEM0002), RRTC on Employment of Individuals with Intellectual and Developmental Disabilities (#90RTEM0003), and Disability Rehabilitation and Research Project on Customized Employment (#90DP0085). The special series consists of 26 articles appearing across four different journals: Journal of Vocational Rehabilitation ; Rehabilitation Counselors and Educators Journal ; Rehabilitation Research, Policy, and Education ; and Rehabilitation Counseling Bulletin .